A temperature-dependent phenology model for Apanteles subandinus Blanchard, parasitoid of Phthorimaea operculella Zeller and Symmetrischema tangolias (Gyen) - Cañedo, V.; Dávila, W.; Carhuapoma, Pablo; Kroschel, Jürgen; Kreuze, Jan F. (Wiley, 2022)
The potato tuber moth (Phthorimaea operculella Zeller) is a major invasive pest of potato (Solanum tuberosum L.) worldwide. Classical biological control using parasitoids had been of primary interest during the last decades to control this pest. More than twenty parasitoid species have been reported parasitizing P. operculella. Apanteles subandinus Blanchard had been successfully used in different countries. Determination of the parasitoid's temperature-dependent development is crucial for better predicting the potential of the parasitoid to establish in a new region and to control the target pest. Therefore, the effect of temperature on the development and reproduction of A. subandinus was studied at five constant temperatures ranging from 11-30 degrees C in its main host P. operculella. The Insect Life Cycle Modeling (ILCYM) software was used to fit nonlinear equations to collected life table data and to establish an overall phenology model to simulate life table parameters based on temperature. The parasitoid completed its life cycle at constant temperatures from 15 to 30 degrees C. Temperature of 11 degrees C was lethal to pupae, and at 35 degrees C no larvae development was possible. The theoretical lower threshold temperatures for the development of egg-larvae and pupae were 10.3 degrees C and 11.8 degrees C respectively. The model predicted limits for survival at around 12 degrees C and 33 degrees C. The lowest senescence rate was observed within the temperature range of 15-25 degrees C. Oviposition time decreased significantly with increasing temperature from 12.2 days (15 degrees C) to 1.8 days (30 degrees C). The highest fertility was predicted at 27 degrees C. Maximum population growth is expected around 26.78 degrees C with a finite rate of increase, lambda of 1.0445, which corresponds to a population doubling time of 15.9 days. The highest values for gross reproduction rate (GRR) and net reproduction rate (R0) were found between 24 and 25 degrees C, and the shortest mean generation time (T) was observed at 30 degrees C (23.48 d). The use of the phenology model in the context of classical biological control of P. operculella is discussed.